In Turkey, The Relationship of Agricultural Sector and Economic Variables: Panel Cointegration Analysis - Peker, Ayşe Esra (My University, 2020)
Hat agricultural sector is examined closer from every point of view and is restructured in complied with the requirements of the age has to be structured comes to our face as a reality any longer accepted by every sector of the society. The various developments experienced in the world in the recent years have directly or indirectly affected agricultural sector. In the economy of Turkey, one of the countries attracting attention with its rapidly growing, there are many theoretical studies dealing with the direct or indirect contribution of agricultural sector.However, it is necessary to increasethe number oftheapplied studies introducing the existing situation of thesector and enabling to develop the effective policies for the sector. For, it is highly important for the theories put forward in theoretical framework to be supported by empirical analyses in terms of forming effective policy suggestions.In the study, the three sub-sectors were considered such as the subsectors of cereal, legume, and fruit-vegetable and the existing situation of the sector was analyzed by moving from the macro variables. In order to identify the effects of macroeconomic variables (inflation, exchange rate, interest, monetary supply), selected in the direction of the aim of the study, panel cointegration test was utilized. Setting off from this point, when the analysis made in the study is examined for all sectors, it was identified that the variable affecting the sector the most was interest rate. When the results of panel cointegration test between interest rate and agricultural production were examined, while there was a negative directional relationship between the production of subsector “fruit vegetable” and the variable “interest” as expected,it attracts attention that therewas a positive relationship between the subsector of cereal legume and interest in contrast to this.
Keywords: Tarımsal Ekonomi ve Politika; Ziraat Mühendisliği; İktisat